GESKIEDENIS VAN DIE MANLIKE EERSGEBOORTE- REGSREëL IN DIE INHEEMSE REG DEEL III: VOORSTELLE VAN DIE SUID-AFRIKAANSE REGSKOMMISSIE - Elmarie Knoetze (Obiter, 2022)
In Part III of this article various statutory implications for and recommendations of the South African Law Reform Commission regarding the male primogeniture rule in the customary law of succession are examined. From the discussion it seems clear that a partial unification of the customary law of succession and the common law is envisaged, in so far as it relates to the inheritance of property. In its most recent proposal the South African Law Reform Commission recommended the reformation of the customary law of succession in legislation aimed at the harmonization of the customary and common law, with the retention of some customary aspects. On the one hand, the South African Law Reform Commission proposals exclude succession in positions of traditional leadership from the proposed reform, but on the other hand the Traditional Leadership and Governance Framework Act 41 of 2003 promotes the principle of gender equality also with regard to positions in traditional leadership.